2013
DOI: 10.2337/dc12-0790
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Development of Proliferative Diabetic Retinopathy

Abstract: OBJECTIVEIdentifying individuals most at risk for diabetic retinopathy progression and intervening early can limit vision loss and reduce the costs associated with managing more advanced disease. The purpose of this study was to identify factors associated with progression from nonproliferative diabetic retinopathy (NPDR) to proliferative diabetic retinopathy (PDR).RESEARCH DESIGN AND METHODSThis was a retrospective cohort analysis using a claims database of all eye care recipients age ≥30 years enrolled in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
98
6
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(114 citation statements)
references
References 39 publications
9
98
6
1
Order By: Relevance
“…Adiponectin has been shown to be significantly higher in T1D patients with severe diabetic retinopathy than in those without, even after adjustment for occurrence of microalbuminuria (Hadjadj et al, 2005). As retinopathy has multiple risk factors it is likely, as is increasingly used for cardiovascular disease and suggested for diabetic nephropathy (Elley et al, 2010;van Dieren et al, 2011;Vergouwe et al, 2010), and more recently for retinopathy (Harris Nwanyanwu et al, 2013) from genetic data Williams et al, 2012). In terms of genetic association the diabetic retinopathy field is less advanced than that for nephropathy, although there have been a number of worthwhile studies (reviewed by (Kuo et al, 2014)).…”
Section: Types Of Biomarkers Include Clinical Biochemical Factors Anmentioning
confidence: 99%
“…Adiponectin has been shown to be significantly higher in T1D patients with severe diabetic retinopathy than in those without, even after adjustment for occurrence of microalbuminuria (Hadjadj et al, 2005). As retinopathy has multiple risk factors it is likely, as is increasingly used for cardiovascular disease and suggested for diabetic nephropathy (Elley et al, 2010;van Dieren et al, 2011;Vergouwe et al, 2010), and more recently for retinopathy (Harris Nwanyanwu et al, 2013) from genetic data Williams et al, 2012). In terms of genetic association the diabetic retinopathy field is less advanced than that for nephropathy, although there have been a number of worthwhile studies (reviewed by (Kuo et al, 2014)).…”
Section: Types Of Biomarkers Include Clinical Biochemical Factors Anmentioning
confidence: 99%
“…A study to identify risk factors associated with the progression to proliferative DR (PDR) identified HbA 1c , diabetic nephropathy, and nonhealing foot ulcers as three risk factors that can help predict progression to PDR. From this, the authors derived a risk score [9]. However, most of the risk for retinopathy is not accounted for by traditional clinical indices [10].…”
Section: Risk Factorsmentioning
confidence: 99%
“…For example, the presence of diabetic foot ulcers is positively correlated with DR as well as with several signs of systemic inflammation, including markedly elevated serum TNF-α levels [160,161]. Recently, Nwanyanwu et al retrospectively studied a group of 4,617 insurance beneficiaries initially diagnosed with nonproliferative DR and found that the presence of non-healing foot ulcers was the best single risk indicator for their progression to PDR [162]. These ulcers were associated with a 54% increase in the chance of progression.…”
Section: Additional Cytokines In Drmentioning
confidence: 99%